1982
DOI: 10.1002/ccd.1810080309
|View full text |Cite
|
Sign up to set email alerts
|

Right atrial myxoma with atrial septal defect: A case report and review of the literature

Abstract: We report the case of a 63-year-old woman presenting with progressive dyspnea of insidious onset culminating in severe central cyanosis. Conventional studies including M-mode echocardiography did not point to the diagnosis. At cardiac catheterization a large right atrial myxoma producing partial dynamic tricuspid obstruction was discovered along with an atrial septal defect with a right to left shunt. After successful surgical excision of the tumor and repair of the atrial septal defect, the patient has been t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Biatrial myxomas are increasingly being reported 11 . In a study, the possibility of the right atrial myxomas and atrial septal defect has been discussed 12 . Our results are also consistent with the literature reviews as the left atrium is the most frequent location and the rarity of ventricular distribution.…”
Section: Discussionsupporting
confidence: 89%
“…Biatrial myxomas are increasingly being reported 11 . In a study, the possibility of the right atrial myxomas and atrial septal defect has been discussed 12 . Our results are also consistent with the literature reviews as the left atrium is the most frequent location and the rarity of ventricular distribution.…”
Section: Discussionsupporting
confidence: 89%
“…Nowadays, the tumours are usually diagnosed with echocardiography, magnetic resonance imaging, and cardiac catheterization. 6,7 When found, surgical excision is the treatment of choice, being indicated when the tumour causes either arrhythmias or intracardiac obstruction. 3,8 We describe here the finding of a giant ventricular fibroma co-existing with an atrial septal defect in an adolescent female.…”
Section: Ardiac Tumours Can Be Either Primary Ormentioning
confidence: 99%
“…When found, fibromas are usually present on the left ventricular free wall, with fewer than one-tenth involving the atriums, even then with a low risk of embolization. Nowadays, the tumours are usually diagnosed with echocardiography, magnetic resonance imaging, and cardiac catheterization 6 , 7 . When found, surgical excision is the treatment of choice, being indicated when the tumour causes either arrhythmias or intracardiac obstruction 3 , 8 .…”
mentioning
confidence: 99%
“…2 A review of 312 cases of right and left atrial myxomas revealed that only two were associated with atrial septal defect. 3 Natarajan et al, 4 reported one case. Right atrial myxoma is rare and the usual signs are right-sided heart failure and pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%